Recovering Quantum Coherence of a Cavity Qubit Coupled to a Noisy Ancilla through Real-Time Feedback - Uri Goldblatt; Nitzan Kahn; Sergey Hazanov; Ofir Milul; Barkay Guttel; Lalit M. Joshi; Daniel Chausovsky; Fabien Lafont; Serge Rosenblum (Physical Review X)
Decoherence in qubits, caused by their interaction with a noisy environment, poses a significant challenge to the development of reliable quantum processors. A prominent source of errors arises from noise in coupled ancillas, which can quickly spread to qubits. By actively monitoring these noisy ancillas, it is possible to not only identify qubit decoherence events but also to correct these errors in real time. This approach is particularly beneficial for bosonic qubits, where the interaction with ancillas is a dominant source of decoherence. In this work, we uncover the intricate dynamics of decoherence in a superconducting cavity qubit due to its interaction with a noisy transmon ancilla. By tracking the noisy ancilla trajectory and using real-time feedback, we successfully recover the lost coherence of the cavity qubit, achieving a fivefold increase in its pure dephasing time. Additionally, by detecting ancilla errors and converting them into erasures, we improve the pure dephasing time by more than an order of magnitude. These advances are essential for realizing long-lived cavity qubits with high-fidelity gates, and they pave the way for more efficient bosonic quantum error-correction codes.